Telomere Length and Insulin Resistance - You, PhD, Nai-chieh Yuko; Song, MD, ScD, Yiqing; Liu, MD, ScD, Simin (North American Journal of Medicine and Science, 2010)
In humans, telomeres are repeating strings of TTAGGG sequences that protect chromosomal ends and maintain genomic stability. Telomere length is considered a critical marker of biological aging because telomeric DNA progressively shortens in dividing somatic cells and contributes to cell senescence, apoptosis, or neoplastic transformation. Recent studies have associated telomere shortening with insulin resistance and various age-related pathological conditions. In this review, we summarized the current available evidence concerning the role of telomere length in the development of insulin resistance.